Variation in symptom distress in underserved Chinese American cancer patients. Issue 18 (8th June 2015) - Dhingra, Lara K.; Lam, Kin; Cheung, William; Shao, Theresa; Li, Zujun; Van de Maele, Sandra; Chang, Victor T.; Chen, Jack; Ye, Huiyan; Wong, Rhoda; Lam, Wan Ling; Chan, Selina; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Cancer is prevalent in the rapidly growing Chinese American community, yet little is known about the symptom experience to guide comprehensive treatment planning. This study evaluated symptom prevalence and patient subgroups with symptom distress in a large sample of Chinese American cancer patients. METHODS Patients were consecutively recruited from 4 oncology practices, and they completed a translated cancer symptom scale. Latent class cluster analysis was used to identify subgroups of patients with distinct symptom distress profiles. RESULTS There were 1436 patients screened; 94.4% were non–English‐speaking, and 45.1% were undergoing cancer therapy. The cancers included breast (32.6%), lung (14.8%), head and neck (12.5%), and hematologic cancer (10.1%). Overall, 1289 patients (89.8%) had 1 or more symptoms, and 1129 (78.6%) had 2 or more. The most prevalent symptoms were a lack of energy (57.0%), dry mouth (55.6%), feeling sad (49.3%), worrying (47.5%), and difficulty sleeping (46.8%). Symptoms causing "quite a bit" or "very much" distress included difficulty sleeping (37.9%), a lack of appetite (37.2%), feeling nervous (35.8%), pain (35.2%), and worrying (34.0%). Four patient subgroups were identified according to the probability of reporting moderate to high symptom distress: very low physical and psychological symptom distress (49.5%), low physical symptom distress and moderate psychological symptom distress (25.2%), moderate physical and psychological symptom distress (17.4%), and high physical and psychological symptom distress (7.8%). CONCLUSIONS Symptom prevalence is high in community‐dwelling Chinese American cancer patients, and nearly half experience severe distress (rated as "quite a bit" or "very much" distressing) from physical symptoms, psychological symptoms, or both. These data have important implications for the development of effective symptom control interventions. Cancer 2015. © 2015 American Cancer Society. Cancer 2015;121:3352–3359. © 2015 American Cancer Society.